O consumo na sociabilidade do capital: expressão de alienação humana? - Oliveira, Rogério Azevêdo de (2018)
This dissertation aims to analyze consumption as an expression of human alienation. From the analyzes of the real, the particularity of the relation of man to the phenomenon of consumption in the present day, we seek to reveal how alienation, through consumption relations, is shown in the daily life of men. This common activity in the life of beings in general, as consumers of the natural materials transformed by work, gains particularity and complexity in the life of the social being and in the dynamics of society, particularly in capitalism. In this sense, we try to reveal and demonstrate the causes and consequences of superfluous, exaggerated and inhuman consumption in the contemporary world, one of the most present expressions of alienation in human sociability. Under the rule of capital, it brings devastating consequences to the lives of men, appropriating their lifetime in production or consumption. We expose the decisive ideological role of advertising when it comes to the manipulation of the conscience of men, as they consume more and more, favoring the expanded reproduction of capital. Finally, starting from the assumption that every human act is an act of prior-ideation that has its ontological origin unleashed by labor, we will attempt to demonstrate the alienated work, according to Marx, as well as the dialectical relation between production, distribution, exchange and consumption, always based on the relations of production of capitalist society, which were determined within the contradictory process of constitution of the social being. We have as fundamental theoretical basis Marx and Lukács, as well as other authors. We take as reference the categories of ter, manipulation and reification, and their immanent relationship with consumption. Our exposition is based on Lukács's postulates, which considers consumption as na expression of alienation in the process of reproduction of individuals and society.